Pectin extraction from banana pere peel at various extraction times - Musafira, Musafira; Fardinah, Fardinah; Fatimah, Meryta Febrilian; Dzulkifli, Dzulkifli; Mulyani, Andi Siti (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2024)
For many years, West Sulawesi's signature plant, banana pere, has only been eaten as fruit, while its peel is often discarded as waste or used as animal feed. This study provides information on the utilization of banana pere peel in order to increase its economic value through the utilization of pectin content contained in banana pere peel. This study aims to extract pectin from banana pere peel (Loka Pere) by using the citric acid solvent extraction method. The extraction process was carried out using 5 variations of time, namely 30, 60, 90, 120 and 150 minutes. The results showed that the use of extraction time for 90 minutes resulted in a yield value of 53.11%, moisture content of 1.15%, ash content of 1.56%, methoxyl content of 2.66% and galacturonic content of 30.88%.